The Role of Measurement Tools in Strengthening Evaluation Practices in Educational Settings in the South-South Region of Nigeria - Voke, Eyetan (dialektika kontemporer, 2025)
This study examined the use of measurement tools in improving evaluation practices in secondary schools across the South-South region of Nigeria. A descriptive survey design was employed, involving 582 secondary school teachers selected from six states: Akwa Ibom, Bayelsa, Cross River, Delta, Edo, and Rivers. Data were collected using a structured questionnaire addressing the types of tools used and their perceived effectiveness. Results showed that teachers frequently use classroom-based tests and rating scales, while diagnostic and technology-based tools are rarely implemented. A positive correlation (r = 0.674, p < 0.05) was observed between the use of standardized tools and the quality of evaluation. Regression analysis indicated that teacher training significantly influences effective assessment practices (R² = 0.454, p < 0.05). The study recommends sustained capacity-building programs for teachers and increased attention to locally developed assessment tools to improve evaluation reliability and relevance in the region.